Bifunctional Z-Scheme Ag/AgVO3/g-C3N4 photocatalysts for expired ciprofloxacin degradation and hydrogen production from natural rainwater without using scavengers - Samsudin, M.F.R. (Academic Press, 2020)
To maximize the employment of sustainable solar energy in treating the recalcitrant pollutant and hydrogen energy production, the development of a highly efficient photocatalyst is desirable. Herein, a Z-scheme Ag/AgVO3/g-C3N4 photocatalyst was synthesized via a wet-impregnation method. The amount of Ag/AgVO3 deposited onto g-C3N4 has a significant effect on the photocharge carrier separation and migration of the as-developed Z-scheme photocatalyst. It was found that 0.5 wt Ag/AgVO3/g-C3N4 photocatalyst exhibited a profound photocatalytic degradation performance with 82.6 ciprofloxacin removal and 3.57 mmol/h of hydrogen produced from natural rainwater under visible-light irradiation. Additionally, the apparent quantum efficiency (AQE) of this sample was 9.95 at 420 nm which is four times higher than the pure sample. The remarkable photocatalytic performance was attributed to the enhanced crystallographic structure, evidently from the XRD and XPS analysis. Moreover, the intimate contact between Ag/AgVO3 and g-C3N4 nanoparticles allows the smooth photocharge carrier separation and migrations, resulting in superior photocatalytic performance in comparison to the pure samples. Interestingly, the profound photocatalytic activity demonstrated here was achieved without the addition of any sacrificial reagents. This work demonstrates the feasibility of utilizing visible-light-driven photocatalysts in treating the recalcitrant antibiotic pollutants and producing hydrogen from natural rainwater. Â© 2020